Recomendação de nitrogênio, fósforo e potássio para girassol sob sistema plantio direto no Paraguai - Villalba, Enrique Oswin Hahn (2008)
Sunflower crop has some important agronomic characteristics, as great fitomassa production, larger resistance to the drought, cold and heat than most of the cultivated species and wide adaptability to different conditions of soil and climates. Its deep root system provides absorption of nutrients of the deepest layers, ciclying great amounts of nitrogen (N), phosphorus (P) and potassium (K). The area cultivated with sunflower had great expansion in the last years in Paraguay, but still does not have a recommendation for N, P and K for the producers regions. The objective of this work was to elaborate a first recommendation of fertilizers for sunflower under no-till system in Paraguay, establishing critical tenors for P and K in the soil in different textural classes, seeking to add sunflower crop as an option, inside of a system of fertilizing the soil for crops in succession, under system direct planting in Paraguay. Experiments were carried out in the departments Misiones and Itapúa in the harvest 2006/2007. For determination of the chemical attributes ten sub-samples were made, composing one soil sample per plot, collected in the depth of 0-0,10 m. Were determined the plants answer (relative productivity) to the doses of maximum economical efficiency (MEE), the critical tenor in the soil for P and K (determined by Mehlich 1 analysis method). The experimental design was random blocks with four repetitions. The treatments consisted of doses of N (0, 25, 50, 75, 100, 125) kg ha-1, using urea as N source, doses of P (0, 40, 80, 120, 160, 200) kg ha-1 of P2O5 (triple superphosphate), doses of K (0, 30, 60, 90, 120, 150) kg ha-1 of K2O (potassium chloride). The elements that were not in study were supplied appropriately in each treatment. The P critical tenor for Itapúa was 14.4 mg dm-3 and for Misiones was of 15.5 mg dm-3. For K the critical tenor found for sunflower crop was 81.5 mg dm-3. These critical tenors were similar to the obtained for soybean, corn and wheat crops in the region. The fertilization recommendations were elaborated for expectation of 2000 kg ha-1 of grains. For soils with smaller tenor than 2% of organic matter are recommended 60 kg ha-1 of N, between 2 and 3% 45 kg ha-1 of N and larger than 3% 30 kg ha-1 of N. Para P fertilization in the respective classes of P fertility that are "very low", "low", "medium", "high" and "very high", they correspond the application of 90, 70, 50, 35 and 20 kg ha-1 of P205 and the recommendations K fertilization are 120, 90, 60, 45 and 30 kg ha-1 of K2O, respectively for the same classes of fertility of very low to very high.